DEVELOPMENT, CHARACTERIZATION AND ANTIBACTERIAL PROPERTIES OF SILVER NANOPARTICLES LOADED SODIUM ALGINATE/XANTHAN GUM MICROBEADS FOR DRUG DELIVERY APPLICATIONS - RAMANA, E. VENKATA; NASEEM (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of this study is to create pH-responsive drug carriers, which are useful because they have the potential to improve treatment efficacy by controlling the release rate of ofloxacin from the polymer matrix. Methods: In the first step, silver nanoparticles (Ag NPs) were synthesized from silver nitrate using leaf extract of phyllanthus urinaria L as a reducing agent. In the second step, Ag-NPs-loaded polymeric microbeads were synthesized using sodium alginate (SA) and xanthan gum (XG) for controlled release of ofloxacin (OFLX). The developed microbeads were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (X-RD), transition electron microscopy (TEM), Selected Area Electron Diffraction (SAED), and scanning electron microscopy (SEM). Swelling and in vitro release studies were performed at pH 2.0 and 7.4 at 37 °C. The in vitro antibacterial activity of microbeads were tested against S. mutans, K. pneumoniae, and B. subtilis. The release kinetics and mechanism were analyzed by fitting the release data into different kinetic models and the korsmeyer-peppas equation. Results: FTIR confirms the generation of silver nanoparticle and also the generation of polymeric microbeads. SEM studies reveal the developed microbeads are spherical in shape with rough surfaces. TEM studies reveal the size of 20-40 nm. XRD analysis reveals the molecular dispersion of DOX and the presence of silver nanoparticles in the polymeric matrix. Investigations of in vitro release and swelling studies show that the developed microbeads are relatively suitable for intestinal drug delivery because higher release rate was observed at pH 7.4. The developed microbead follows non-Fickian diffusion drug release mechanism. The created samples exhibited antimicrobial activity against S. mutans, K. pneumoniae, and B. subtilis. Conclusion: The results indicate that microbeads containing OFLX and silver nanoparticles are effective drug-delivery vehicles. A further warrant is required for the use of manufactured microbeads in drug delivery applications.